Educational research, policymaking and practice - Hammersley, Martyn (London : Paul Chapman, 2002)
The issue of the relationship between educational research and policy-making or practice has been a perennial concern. This book deals with some basic and controversial questions about the issue.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Education -- Research; Education and state